"I Used to Care but Things Have Changed": A Genealogy of Compassion in Organizational Theory. (October 2014) - Simpson, Ace V.; Clegg, Stewart; Pitsis, Tyrone
We explore the use of compassion as a technology of power and subjectivity within organizations. Using a genealogical method, we trace the history of concern with compassion in organizations as a mode of employee discipline. The article applies a perspective developed from Foucault, focused on power/knowledge relations and the role that they play in the formation of the subject in organizations. Organizational compassion has been constantly re-defined and re-evaluated according to changing organizational objectives for shaping employee subjectivity. While one may think of compassion as a "good" phenomenon, we counsel caution against doing so in all contexts as a generic endorsement of a "positive" agenda. As we show, compassion may be a mode of power.